Passive cooling technology for photovoltaic panels for domestic houses - Wu, Shenyi; Xiong, Chenguang (Oxford University Press, 2014)
The efficiency of photovoltaic panels decreases as the panels' temperature increases, which results in deduction of electricity generation. In order to reduce this effect, different cooling methods were proposed and investigated. This paper reviews the previous work on cooling PV cells and concludes that the cost-effectiveness, design feasibility and minimal energy consumption are the important design consideration for cooling systems. Based on these considerations, this paper reports a passive cooling method that utilizes rainwater as cooling media and a gas expansion device to distribute the rainwater. The gas is thermally expanded from receiving solar radiation as such the amount of water it pushes to flow over the PV cells is proportional with the solar radiation it received. The paper reports a design and simulation of such a system for a domestic house application. In the paper, a relationship of the gas chamber size, solar radiation and gas expansion volume was established for evaluation with respect to the variation of gas temperature and the amount of rainwater used for cooling. A heat transfer model was used to evaluate the performance of the cells by cooling with this passive device. The results show that on a design day, the passive cooling system reduces the temperature of the cells and increases electrical efficiency of the PV panel by 8.3%. The payback period of this system is <14 years.